Consumer information sharing understanding psychological drivers of social transmission - Akpinar, Ezki (Erasmus University Rotterdam, 2013)
Consumers often share experiences, opinions or certain content with others. For example, they suggest restaurants, recommend article posts, share online videos, pass along rumors and complain about customer services. Such word of mouth determines what catches on and become popular among consumers. While research has shown that word of mouth is frequent and important, there has been limited work on understanding what makes certain content more shared than others. This dissertation fills this gap, and explores the psychological drivers that shape consumer information sharing and more broadly cultural success. It integrates various research perspectives and illustrates certain characteristics that make people share some content more than others. First, we study how self-relevance (i.e., high vs. low) impact sharing behavior of product harm information, and this process is moderated by consumer self-construal (independent vs. interdependent). Second, we examine how advertising content can get viral, and how and when this benefits the brand. Finally, we explore how phrases that relate to senses in metaphoric ways (e.g., cold person) lead to higher recall, which contributes their cultural success over time. The practical implications of this dissertation are of interest for professionals in the area of marketing, advertising, and public policy making. From a theoretical point of view, this dissertation has a cross-disciplinary contribution, and relates to the fields of health psychology, advertising, persuasion knowledge, linguistics, embodied cognition and foundations of culture.